Physiological Roles of Serotonin in Bivalves: Possible Interference by Environmental Chemicals Resulting in Neuroendocrine Disruption - Canesi, Laura; Miglioli, Angelica; Balbi, Teresa; Fabbri, Elena (Frontiers in Endocrinology, 2022)
Contaminants of Emerging Concerns (CECs) are defined as chemicals not commonly monitored in aquatic ecosystems, but with the potential to cause adverse effects on biota. CECs include Endocrine Disrupting Chemicals (EDCs) and Neuro-Endocrine disruptors (NEDs) of vertebrates. However, most invertebrates only rely on neuroendocrine systems to maintain homeostatic processes. Although conserved neuroendocrine components have been characterized in ecologically relevant groups, limited knowledge on invertebrate neuroendocrinology makes it difficult to define EDCs and NEDs in most species. The monoamine serotonin (5-hydroxytryptamine, 5-HT) acts both as a neurotransmitter and as a peripheral hormone in mammals. In molluscs, 5-HT is involved in multiple physiological roles and molecular components of the serotonergic system have been identified. This review is focused on the effects of CECs on the serotonergic system of bivalve molluscs. Bivalves are widespread in all aquatic environments, estuarine and coastal areas in particular, where they are exposed to a variety of chemicals. In bivalves, 5-HT is involved in gametogenesis and spawning, oocyte maturation and sperm motility, regulates heart function, gill ciliary beating, mantle/siphon function, the ‘‘catch’’ state of smooth muscle and immune responses. Components of 5-HT transduction (receptors and signaling pathways) are being identified in several bivalve species. Different CECs have been shown to affect bivalve serotonergic system. This particularly applies to antidepressants, among the most commonly detected human pharmaceuticals in the aquatic environment. In particular, selective serotonin reuptake inhibitors (SSRIs) are frequently detected in seawater and in bivalve tissues. Information available on the effects and mechanisms of action of SSRIs on the serotonergic system of adult bivalves is summarized. Data are also reported on the effects of CECs on development of neuroendocrine pathways of early larval stages, in particular on the effects of model EDCs in the marine mussel Mytilus galloprovincialis. Overall, available data point at the serotonergic system as a sensitive target for neuroendocrine disruption in bivalves. The results contribute drawing Adverse Outcome Pathways (AOPs) for model EDCs and SSRIs in larvae and adults. However, basic research on neuroendocrine signaling is still needed to evaluate the potential impact of neuroendocrine disruptors in key invertebrate groups of aquatic ecosystems.